Transitional justice as neoliberal apparatus: power, subjectivity and sacrificial violence - Bowsher, Josh (2016)
This thesis aims to critically conceptualise the relationship between transitional justice and the project of neoliberal globalisation, which, since the end of the Cold War, has sought to transform post-conflict societies according to economic logics that emphasise individualism, enterprise and competition. In the last 25 years, Transitional justice has risen to the forefront of the human rights movement, and is now firmly embedded in the institutions of global neoliberal governance such as the UN, the International Monetary Fund (IMF), and the World Bank. Normatively conceived as an ‘apolitical’ set of technocratic mechanisms, the relationship between transitional justice and processes of ‘neoliberalisation’, which are often a significant part of post-conflict transitions, remains largely undertheorised by scholars and practitioners. Addressing this problem, the thesis follows two interrelated lines of enquiry. First, with reference to the work of Michel Foucault, the thesis conceptualises transitional justice as an apparatus (dispositif) with a set of practices that support the process of neoliberal transition. Secondly, by drawing on René Girard’s theory of sacrifice, the thesis shows that the central mechanisms of the apparatus, that is, trials and truth commissions, are practices of ‘sacrificial violence’ designed to expel the ‘evil’ of the past and lay a foundation for the neoliberal society that comes after. Using the transitions of Rwanda, South Africa, and Sierra Leone as case studies, the thesis demonstrates that these practices of sacrificial violence produce narratives and engender subjectivities that support and prefigure neoliberal transitions designed to reconstitute war-torn states as market societies.